Professional practice for landscape architects Nicola Garmory, Rachel Tennant, and Clare Winsch. - Garmory, Nicola (Architectural Press, 2002)
The book deals with the practical issues of being successful in the landscape design business. It provides a framework of the issues that underlie the work of landscape architects in business and in law. Collected into one volume are all the relevant but diverse legal, business and practical contract management themes of the Professional Practice examination. Valuable information is presented in easy-to-follow line diagrams and flow charts.Topics covered include Landscape Practice, Liability and the Law, Planning Legislation, Environmental Legislation, Tendering and Contract Administration.